PEMBELAJARAN AL-QUR'AN UNTUK ANAK USIA DINI MELALUI METODE QIROAH - Ardina Risdiyana; Laili Sofwaturrohmah; Maulia Dwi Apriani; Sutrimo Purnomo (PT. Cadas Insan Madani, 2026)
This research is motivated by the importance of learning the Quran from an early age as a foundation for reading fluently, fluently, and in accordance with the rules of tajweed. Early childhood is a golden period of development, so appropriate, engaging learning methods are needed that are tailored to the child's characteristics. This study aims to determine the application of the Qiro'ah method in Quran learning and its effectiveness in improving children's reading skills. The study used a qualitative descriptive approach, with subjects including TPQ administrators, teachers, parents, and students. The object of the study was the process of learning the Quran through the Qiro'ah method. Data collection techniques were conducted through observation, interviews, and documentation, then analyzed using qualitative descriptive techniques to obtain a comprehensive picture. The results indicate that the Qiro'ah method has significant potential for gradually improving children's Quran reading skills, particularly in aspects of pronunciation, fluency, and beauty of recitation. This method is effective because it is implemented regularly and repeatedly, and is tailored to the learning needs of early childhood, which requires a concrete, fun, and interactive approach. Besides being a basic method, Qiro'ah is also used as a follow-up to the Iqro method to improve reading fluency and embellishment. However, several obstacles exist, such as limited teaching staff, lack of teacher training, differences in student abilities, and economic factors affecting textbook availability. Other challenges stem from the low interest in learning among older children and the influence of gadgets. Despite this, learning continues to progress thanks to teacher creativity, parental support, and a conducive learning environment. The Qiro'ah method has the potential to be an effective strategy if supported optimally and sustainably.